External Parasites of Small Ruminants A Practical Guide to their Prevention and Control - Bates, Peter (CABI, 2014)
Sheep and goats (collectively termed small ruminants - or small stock) were the first livestock to be domesticated, in central Asia, over 10,000 years ago, and are both currently widespread throughout the world. In 2005, there were 1,001,351,000 breeding sheep in the world (Table 1.1), with the larg- est population found in China (147,000,000) and 23,933,000 found in the UK (BWMB, 2006). According to FAO statistics, by 2007 the world breeding sheep population had increased to 1,112,520,621 and there were 850,219,925 breeding goats in 2007 (www. fao.org/corp/statistics/en), with the largest populations recorded in China (183 million) and India (120 million) (www.fao.org/ag). Within Europe, Greece has the largest number of goats (5 million), followed by Spain (3 million) and France (1 million). In the UK, there are approximately 98,000 goats (Harwood, 2008).